Damage evolution and rupture time prediction in thermal barrier coatings subjected to cyclic heating and cooling: an acoustic emission method - Yang, L.; Zhou, Y.; Lu, Chungsheng (Elsevier Ltd, 2011)
The real-time testing and quantitative assessment of damage evolution in thermal barrier coatings (TBCs) is desirable, but still intractable, especially at elevated temperature. In this paper, the fracture process of TBCs subjected to cyclic heating and cooling is monitored using an acoustic emission method. Based on the wavelet analysis of acoustic emission signals, damage modes in TBCs are discriminated. The results show that, due to thermal stress, it is preferential for vertical cracks in the heating stage and interface cracks in the cooling stage. The surface crack density and interface crack length are calculated to obtain the quantitative correlation of damage evolution in TBCs and acoustic emission parameters. The rupture time of TBCs can be predicted by the statistical analysis of acoustic emission signals.